Curcumin and berberine co-loaded liposomes for anti-hepatocellular carcinoma therapy by blocking the cross-talk between hepatic stellate cells and tumor cells - Jingliang Wu; Cuiping Qi; Cuiping Qi; Hao Wang; Qing Wang; Jingui Sun; Jinping Dong; Guohua Yu; Zhiqin Gao; Bo Zhang; Guixiang Tian (Frontiers Media S.A., 2022)
Cancer-associated fibroblasts (CAFs) are a major component of the tumor microenvironment (TME). In hepatocellular carcinoma (HCC), quiescent hepatic stellate cells (HSCs) could be activated to become CAFs, which play a critical role in tumor progression and drug resistance. Therefore, recent efforts have been focused on combining anti-HSC and pro-apoptotic activities to improve anti-tumor efficacy of drugs. In this study, glycyrrhetinic acid and hyaluronic acid-modified liposomes (GA-HA-Lip) were prepared for co-delivery of curcumin (CUR) and berberine (BBR) for the treatment of HCC. Furthermore, we established the LX-2+BEL-7402 co-cultured cell model and implanted the m-HSCs+H22 cells into a mouse to evaluate the anti-tumor effect of CUR&BBR/GA-HA-Lip both in vitro and in vivo. The results showed that CUR&BBR/GA-HA-Lip could accumulate in tumor tissues and be taken up by HSCs and BEL-7402 cells simultaneously. Compared with free CUR, the combination therapy based on GA-HA-Lip exhibits stronger pro-apoptotic and anti-proliferation effect both in vitro and in vivo. The anti-tumor mechanistic study revealed that CUR&BBR/GA-HA-Lip could inhibit the activation of HSCs and restrain drug resistance of tumor cells. In summary, CUR&BBR/GA-HA-Lip could be a promising nano-sized formulation for anti-tumor therapy.